Peculiarities of Thunderstorms’ Occurrences on the Border of the Western Siberia Plains and Altai Mountains - KOCHEEVA, Nina A.; CHANKIBAEVA, Muhabat H.; MINAEV, Aleksandr I.; SUKHOVA, Maria G.; MODOROV, Anton A. (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017, 2018)
Mountains of Altai are characterized by the greatest elevation in the Siberian region, creating an obstacle for Western air masses transfer. This fact determines the diversity of micro-climatic conditions. Complex climatic and geomorphologic factors create the variety of storms in certain regions of the mountainous country. At the same time, the climate and the weather in the mountains of Altai is the product of processes of general atmospheric circulation. Any economic activity feels the risk during storms. The airport on the territory of the Altai Republic which receives a lot of passengers, especially in the summer, operates again. Therefore, it is rational to conduct the study of the relationship of thunderstorm activity with cyclonic activity, which was the purpose of the study, on the Northern slopes of the Altai, where the airport and the weather station are situated. The results of the study allowed identifying the periods of thunderstorms’ manifestation on the border of the plains of Western Siberia and the Altai Mountains, as well as their confinement to the frontal phenomena.